Factors to Pay Attention to and Problems in Implementing a Franchise Business Agreement - Maryam, Sintia; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
The development of trade in the era of globalization is increasing rapidly, one way to improve people's welfare is to do entrepreneurship, because entrepreneurship will make society self-sufficient and with entrepreneurship will open opportunities for themselves and take advantage of the opportunities created. With a franchise system, franchisees only buy an existing business system and have the advantage that the buyer of the system does not need to start from scratch. Of course, to realize the franchise is marked with a franchise agreement in order to minimize future irregularities. This type of research method in writing is qualitative with the type of document. Qualitative research is a type of research whose results are not based on statistics or other calculations. The purpose of this writing is to find out the problems in implementing the rights and obligations of the parties to the agreement and what factors must be considered by the parties outside the script in implementing the franchise agreement.